Mapping the Potential and Distribution of Ecotourism on Ambon Island, Maluku, Indonesia - Leiwakabessy, Fredy; Kubangun, Muhammad Tarmizi; Pattiasina, Eifan Boyke (Sam Ratulangi University, 2026)
Tourism in Indonesia now plays a significant role in providing benefits to the country's economic, social, and cultural activities. The development of nature-based tourism, or what we know as ecotourism, which emphasizes local culture and wisdom, is now being widely considered in various regions to attract tourists. Data management was carried out by analyzing community perception questionnaires related to the potential and distribution of ecotourism in the form of graphs of respondent personal data, ecotourism attractions, ecotourism facilities, community participation, and environmental impacts. Also, inputting tourist location coordinate data into ArcGIS 10.8 software, then creating a database that will be supplemented with non-spatial data. The results of the study, based on a tourist survey and questionnaire results, showed that the 10 ecotourism locations were favored by both local and foreign tourists in terms of facilities, ecotourism location attractions, community participation, and environmental impacts of the ecotourism locations.